Grain Size Characteristics and Transport Pathways of Surface Sediments in Eastern Pamir Plateau - Li Hanlin; He Qing; Zhao Quanwei; Ma Mingjie (Shuitu baochi tongbao)
[Objective] The grain size characteristics and sources of surface sediments in the Eastern Pamir Plateau were analyzed in order to provide a scientific basis for improving the understanding of the sedimentary environment and ecological environment construction in the western plateau of China. [Methods] The particle size characteristics of surface sediments in the Eastern Pamir Plateau were analyzed using a laser particle size analyzer. The influence of remote aeolian sedimentation on the composition of surface sediments was analyzed by use of a backward trajectory model. [Results] The surface sediments in the study area were mainly sand particles. Particle size of the surface sediments decreased with the gradual increase of altitude. It was preliminarily speculated that the surface sediments were mainly lacustrine sediments, and the far-source aeolian settlement was mainly affected by westerly air flow in Central Asia and sand dust particles in the Western Taklimakan Desert. [Conclusion] The Eastern Pamir Plateau is located in a fragile ecological environmental area. Land use planning should be formulated according to local conditions. At the same time, it is necessary to prevent the impact of dust particles on the ecological environment of Central Asia.